Survival of surgically-treated patients with squamous cell carcinoma of the buccal mucosa - Jailani, M.A.; Rahman, Z.A.A. (2007)
Objective: The aim of this study was to establish clinical outcomes from surgical treatment of squamous cell carcinoma of the buccal mucosa in terms of survival rates and disease-free period and their relationships with other variables. Patients and Methods: This survival study of squamous cell carcinoma of the buccal mucosa was done at the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, University of Malaya. The case notes of 55 patients were reviewed retrospectively and the demographic data analysed. Survival rates were determined using the Kaplan-Meier method and the distribution of each variable in the survival studies was analysed by the log rank test. Results: The subjects ranged in age from 42 to 78 years (mean, 61.6 years) and the female-to-male ratio was 6:1. The overall 5-year cumulative survival probability was 49.7. Survival was strongly influenced by tumour stage, neck node involvement, and tumour grade. Conclusion: The treatment outcome of this study is comparable with studies conducted elsewhere. The results emphasise the importance of early detection and intervention in maximising survival in this setting. Â© 2007 Asian Association of Oral and Maxillofacial Surgeons.